Diminishing Efficacy of Combination Therapy, Response-Heterogeneity, and Treatment Intolerance Limit the Attainability of Tight Risk Factor Control in Patients with Diabetes - Timbie, Justin W (Blackwell Science Inc, 2010)
OBJECTIVE: To evaluate the attainability of tight risk factor control targets for three diabetes risk factors and to assess the degree of polypharmacy required. DATA SOURCES/STUDY SETTING: National Health and Nutrition Examination Survey-III. STUDY DESIGN: We simulated a strategy of “treating to targets,” exposing subjects to a battery of treatments until low-density lipoprotein (LDL)-cholesterol (100 mg/dL), hemoglobin A1c (7 percent), and blood pressure (130/80 mm Hg) targets were achieved or until all treatments had been exhausted. Regimens included five statins of increasing potency, four A1c-lowering therapies, and eight steps of antihypertensive therapy. DATA COLLECTION/EXTRACTION METHODS: We selected parameter estimates from placebo-controlled trials and meta-analyses. PRINCIPAL FINDINGS: Under ideal efficacy conditions, 77, 64, and 58 percent of subjects achieved the LDL, A1c, and blood pressure targets, respectively. Successful control depended highly on a subject's baseline number of treatments. Using the least favorable assumptions of treatment tolerance, success rates were 11–17 percentage points lower. Approximately 57 percent of subjects required five or more medication classes. CONCLUSIONS: A significant proportion of people with diabetes will fail to achieve targets despite using high doses of multiple, conventional treatments. These findings raise concerns about the feasibility and polypharmacy burden needed for tight risk factor control, and the use of measures of tight control to assess the quality of care for diabetes.